500+ Benefit as an Element of Pro-Family and Demographic Policy of the Country - Krawczyk, Michał (Management and Administration Journal, 2019)
Starting from April 2016, the legislator introduced a new type of social benefit – raising children & educational benefit. This allowance is for the second and subsequent child, and in the poorest families also for the first. The intention of the government is to provide a benefit helpful in bringing up children, by providing appropriate financial assistance in raising children, to reverse the drop in the number of births observed for many years and to further reduce the scale of poverty among families with the most difficult financial situation. However, after less than three years of application of the 500+ Program, it is difficult to determine unequivocally whether there has been a permanent reversal of the birth declining trend. Statistical data in this area can be interpreted in many ways and more time is needed to attempt a final summary. Certainly, the Program has improved the economic situation of the poorest families, especially those with large children.